Fungsi Kepala Desa Terhadap Pengelolaan Lingkungan Permukiman Masyarakat Desa Di Desa Selat Kecamatan Pemayung Kabupaten Batanghari - Utami, Melyn; Noviades, Dhil's; Zulkarnain, Iskandar (Fakultas Hukum Universitas Jambi, 2022)
A good and healthy environment is a basic right of every Indonesian citizen as mandated in Article 28H of the 1945 Constitution of the Republic of Indonesia. Origin rights, and/or traditional rights recognized and respected in the government system, led by the Head The village as the village government is assisted by the village apparatus as an element of village administration. The Village Head is in charge of administering Village Administration, implementing Village Development, Village community development, and empowering Village communities. Batanghari Regency Regional Regulation Article 113 paragraph (2) Letter f Elucidation in paragraph (2) General Provisions for Zoning Regulations for Settlement Areas other regulations that covering residential areas that have a high density and tend to be slums, it is necessary to improve the environment in a participatory manner in number 2 article 113 paragraph (2) letter f. The purpose of this study is how the function of the village head is to the problems faced in terms of settlements, as well as the development of productive settlements in Selat Village, Pemayung District, Batanghari Regency. The research method used is empirical juridical and qualitatively descriptive with the elaboration and description of the problems regarding the population in the Straits Village.